If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = 6x + -6 Reorder the terms: -8 + x = 6x + -6 Reorder the terms: -8 + x = -6 + 6x Solving -8 + x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -8 + x + -6x = -6 + 6x + -6x Combine like terms: x + -6x = -5x -8 + -5x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + -5x = -6 + 0 -8 + -5x = -6 Add '8' to each side of the equation. -8 + 8 + -5x = -6 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = -6 + 8 -5x = -6 + 8 Combine like terms: -6 + 8 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4
| 3x=4y+-8 | | 6x^3-22x^2+9x=0 | | e^3x=6*e^3*x | | (x-5)(x^2+5x+25)=0 | | 32-2=64 | | 6(3x-2)+9x= | | 3v^2+v+2=0 | | 3t-24+2t=7-1t | | -28-(-8)=x/9 | | 21+-14x=29+x | | (4+w)(5w-9)=0 | | 4p+2p-3x=x | | -9n+10= | | 3c-24=96 | | 3y-8+5(-5)=3(-5)+10 | | -7-3(-6n+8)=-121 | | y+y+5x-4y+7= | | 7(1-4x)=119 | | e^3x=6xe^3 | | 3y-8+5x=3x+10 | | 90=8/5x | | 7(3+4x)-8x=-99 | | 2.5x-1.7*(5-2x)=3x | | -7(-8x+6)+1=295 | | 5x+2y+3p+4y-p= | | 10=ay+3d | | 3t-24+2t=7-t | | 2+5x-1+5x= | | 5t-8=28 | | 14+1=-3(3x-5) | | 10x-3y+3x-4y= | | graphm(x)=5x |